Professional JavaScript for web developers - Zakas, Nicholas C. ([place of publication not identified] : John Wiley and Sons, Incorporation, 2012)
A significant update to a bestselling JavaScript book As the key scripting language for the web, JavaScript is supported by every modern web browser and allows developers to create client-side scripts that take advantage of features such as animating the canvas tag and enabling client-side storage and application caches.
Keywords: WEB SITE DEVELOPMENT; JAVASCRIPT (COMPUTER PROGRAM LANGUAGE)